Intersection 2018. - Lee-Rekers, Alexander (Currency Press, 2018)
Each year ATYP brings together 20 young writers from across the country and challenges them to create stories that speak to the experience of being seventeen years old in Australia, here and now, creating a compelling, complex mosaic of modern life. Critically acclaimed in its first incarnation, it returns to explore the excitement, terror and electricity of being seventeen.